1996
DOI: 10.1017/s1049023x00042461
|View full text |Cite
|
Sign up to set email alerts
|

Portraits of Survival: A 20-year Follow-up of the Children of Buffalo Creek

Abstract: Mississippi. Almost every river feeding the Mississippi from the West was out of its banks for eight weeks or more. Many rivers were a mile or more out of their banks for several weeks. Many levees collapsed and many threatened to do so for several weeks. Homes along smaller rivers re-flooded as many as seven and eight times. People who never were flooded remained out of their homes for several weeks because of threatened levee breaches. Farm crop damage was estimated in the billions of dollars. For many, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In Charleston County, 80% of all structures endured roof damage, 6,000 homes were destroyed, over 12,000 homes were rendered uninhabitable, and 65,000 people required temporary shelter (Mullins & Burbage, 1989). Since Terr's (1981) seminal study on the effects of the Chowchilla bus kidnapping on children, several studies have docu mented short-term negative consequences (Belter & Shannon, 1993;Kendall-Tackett, Williams, & Finkelhor, 1993;Klingman, 1992;Pynoos et al, 1987;Yule & Udwin, 1991) and long-term behavioral and emo tional changes (Conte & Berliner, 1987;Green et al, 1994;Honig, Grace, Lindy, Newman, & Titchener, 1993;Nader, Py noos, Fairbanks, & Frederick, 1990;Vogel & Vernberg, 1993;Yule & Williams, 1990) 1985; Dollinger, 0 'Donnell, & Staley, 1984), and separation anxiety (Dollinger, 1985;Sugar, 1988). Children have also been shown to demonstrate an increase in fears (Bloom, 1986;Dollinger, 1985;Dol linger et al, 1984) and some have exhib ited play involving the traumatic event (Ga lante & Foa, 1986;Saylor, Swenson, & Powell, 1992;Sugar, 1988).…”
mentioning
confidence: 99%
“…In Charleston County, 80% of all structures endured roof damage, 6,000 homes were destroyed, over 12,000 homes were rendered uninhabitable, and 65,000 people required temporary shelter (Mullins & Burbage, 1989). Since Terr's (1981) seminal study on the effects of the Chowchilla bus kidnapping on children, several studies have docu mented short-term negative consequences (Belter & Shannon, 1993;Kendall-Tackett, Williams, & Finkelhor, 1993;Klingman, 1992;Pynoos et al, 1987;Yule & Udwin, 1991) and long-term behavioral and emo tional changes (Conte & Berliner, 1987;Green et al, 1994;Honig, Grace, Lindy, Newman, & Titchener, 1993;Nader, Py noos, Fairbanks, & Frederick, 1990;Vogel & Vernberg, 1993;Yule & Williams, 1990) 1985; Dollinger, 0 'Donnell, & Staley, 1984), and separation anxiety (Dollinger, 1985;Sugar, 1988). Children have also been shown to demonstrate an increase in fears (Bloom, 1986;Dollinger, 1985;Dol linger et al, 1984) and some have exhib ited play involving the traumatic event (Ga lante & Foa, 1986;Saylor, Swenson, & Powell, 1992;Sugar, 1988).…”
mentioning
confidence: 99%
“…The in-depth psychoanalytic evaluations of four of the videotaped interviews examined the participants' initial coping responses to the flood and followed their course. What appeared to be critical was whether the coping response consolidated or involved the integration of adaptive behaviors related to the traumatic experience (Honig et al, 1993). Consolidation appeared to contribute to resiliency and healthy adult psychological functioning; lack of consolidation seemed to contribute to a risk for chronic PTSD.…”
Section: Findings Of the 17-year Follow-up Psychoanalytic Case Studymentioning
confidence: 99%
“…Green, et al (1991) found that the risk factors that best predicted continuing post-traumatic symptomatology was degree of life threat, parental psychopathology, being female and an irritable and or depressed family atmosphere. Honig et al, (1993) observed that there is a spectrum of "adaptational possibilities" found in children 20 years after the Buffalo Creek Disaster which were related to the family's initial response to the disaster and that psychopathology in the children resonated with parental psychopathology.…”
Section: Gender Effectsmentioning
confidence: 99%
“…The psychological effects of natural disaster on children and adolescents has become an emerging focus of study (Lipovsky, 1991). In recent years reports have been published on the psychological responses of children and adolescents to hurricane, fire, earthquake and flood (Bloch et al, 1956;Newman, 1976;Green et al, 1991Green et al, , 1994Bradburn, 1991;Burke et al, 1986;Yacoubian et al, 1989;Garrison et al, 1993;Honig et al, 1993;McFarlane, Policansky & Irwin, 1987;Pynoos et al 1993;Shannon et al, 1994;Shaw et al, 1995). The spectrum of post-traumatic stress symptomatology in children and adolescents generally parallels the psychological responses of adults to overwhelming disaster.…”
Section: Appendix Amentioning
confidence: 99%